2007
DOI: 10.1080/09553000701317341
|View full text |Cite
|
Sign up to set email alerts
|

Ornithine decarboxylase activity is affected in primary astrocytes but not in secondary cell lines exposed to 872 MHz RF radiation

Abstract: ODC activity was affected by RF radiation in rat primary neural cells, but the secondary cells used in this study showed essentially no response to similar RF radiation. In contrast to some previous studies, no differences between the modulated and continuous wave signals were detected. Further studies with primary astrocytes are warranted to confirm the present findings and to explore the mechanisms of the effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 11 publications
0
17
0
1
Order By: Relevance
“…This observation is in agreement with an earlier study on genotoxic effects of 50-Hz electromagnetic fields (ELF-EMF) using the alkaline and neutral comet assay as test systems (Ivancsits et al 2005) In that study three responder (human fibroblasts, human melanocytes, and rat granulosa cells in culture) and three non-responder cell types (human lymphocytes, human monocytes, and human skeletal muscle cells in culture) could be identified. A recent study on ornithine decarboxylase activity after 872 MHz GSM exposure demonstrated a decreased activity in primary but not in secondary rat astrocytes (Höytö et al 2007). This strongly points to the significance of the cell system used when investigating genotoxic effects of EMFs.…”
Section: Discussionmentioning
confidence: 96%
“…This observation is in agreement with an earlier study on genotoxic effects of 50-Hz electromagnetic fields (ELF-EMF) using the alkaline and neutral comet assay as test systems (Ivancsits et al 2005) In that study three responder (human fibroblasts, human melanocytes, and rat granulosa cells in culture) and three non-responder cell types (human lymphocytes, human monocytes, and human skeletal muscle cells in culture) could be identified. A recent study on ornithine decarboxylase activity after 872 MHz GSM exposure demonstrated a decreased activity in primary but not in secondary rat astrocytes (Höytö et al 2007). This strongly points to the significance of the cell system used when investigating genotoxic effects of EMFs.…”
Section: Discussionmentioning
confidence: 96%
“…Two studies reported effects on ODC activity, but the effects were not dependent on modulation. Höytö et al [2007a] reported that ODC activity was decreased in rat primary astrocytes after exposure to 872 MHz RF fields, but there were no differences between CW and GSMmodulated signals. Also, there were no differences between CW and Digital Advanced Mobile Phone System (D-AMPS) signals in another study, in which enhancement of ODC activity was observed in L929 cells exposed at 872, but not at 835 MHz in another exposure system [Höytö et al, 2007b].…”
Section: In Vitro Studies On Cancer-relevant Non-genotoxic Effectsmentioning
confidence: 94%
“…For other abbreviations, see Tables 1-2. increased cell proliferation and is increased by many tumour promoters. ODC activity was unaffected in human SH-SY5Y neuroblastoma cells [Höytö et al, 2007a;Billaudel et al, 2009a], murine L929 fibroblasts [Höytö et al, 2006[Höytö et al, , 2007a[Höytö et al, ,b, 2008bBillaudel et al, 2009b] and rat C6 glioblastoma cells [Höytö et al, 2007a] exposed to RF energy using various exposure levels and modulation characteristics. Two studies reported effects on ODC activity, but the effects were not dependent on modulation.…”
Section: In Vitro Studies On Cancer-relevant Non-genotoxic Effectsmentioning
confidence: 99%
“…Controversial results have been obtained from studies on RF radiation effects on ODC activity in L929 cells. Some reports have indicated increased ODC activity in cells exposed to a 835 MHz Digital advanced mobile phone system (DAMPS, 50 Hz modulated) signal (Litovitz et al 1993, whereas some studies were not able to confirm these results with or without DAMPS modulation (Desta et al 2003, Hö ytö et al 2007b), or with CW or GSM signal at 900 MHz (Hö ytö et al 2006 or at 872 MHz (Hö ytö et al 2007a). Desta et al (2003) reported decreased ODC activity after RF radiation exposure at SAR levels over 6 W/kg, but the temperature increase in cell cultures was shown to cause this effect, and this was further confirmed by our previous work (Hö ytö et al 2006).…”
Section: Discussionmentioning
confidence: 94%